A Novel Idea to Reduce the Consumption of Povidone-iodine in the Operation Theater: A Need of the Hour for Developing Countries - Vetrivel Chezian Sengodan; Kumaravel Ramakrishnan; Saisarrvesh Purushothaman; Karthikeyan Kandasamy; Murugesh Munusamy (Journal of Orthopedics and Joint Surgery)
Introduction: Surgical site infection (SSI) is the most common hospital-related infection in developing countries. Antiseptics are used to prevent SSIs. Iodine, alcohol, and chlorhexidine are commonly used for preoperative skin preparation. Of these, povidone-iodine is most commonly used in the operation theater. Aim and objective: Our study aims to compare the quantity of povidone-iodine used in operation theater by a conventional method with the measurable spraying device method. Materials and methods: This prospective study was conducted in Government Coimbatore Medical College Hospital at Institute of Orthopedics and Traumatology, Coimbatore, Tamil Nadu from 2018 to 2019 in its four elective theaters and one 24 × 7 emergency operation theater. We sprayed povidone-iodine over the skin during the preoperative skin preparation and calculated the usage for every patient with measurement in the bottle and compared it with the conventional method of skin preparation with the gauze soaked in povidone-iodine solution in a sterile bowl. Results: The average amount of povidone-iodine solution used per case for the years 2018 and 2019 were 120.08 and 35.83 mL, respectively, thereby reducing 70% of the usage of povidone-iodine consumption. Conclusion: By using a transparent spraying bottle with measurement on the container, the quantity of povidone-iodine utilization in the operating room can be drastically reduced, thereby reducing the cost spent for antiseptics in health care.